The reliability of radiostereometric analysis in determining physeal motion in slipped capital femoral epiphysis in standard uniplanar and low-dose EOS biplanar radiography: a phantom model study. Issue 6 (November 2018) - Hurry, Jennifer K.; Rehan, Saad; Spurway, Alan J.; Laende, Elise K.; Astephen Wilson, Janie L.; Logan, Karl J.; Dunbar, Michael J.; El-Hawary, Ron
Abstract : Physeal closure after slipped capital femoral epiphysis fixation can be difficult to assess on two-dimensional conventional radiographs. Radiostereometric analysis offers improved motion detection over conventional radiography, whereas the EOS biplanar imager provides a means for low radiation weight-bearing images. This phantom study assessed the reliability of measuring motion using radiostereometric analysis in the EOS using a slipped capital femoral epiphysis model. The accuracy and precision were better than 0.09±0.05 mm and 0.20°±0.36° when centered in the imaging space, were within the limits of clinical significance, and were not different from a standard uniplanar radiostereometric system. Abstract : Supplemental Digital Content is available in the text.